The Kingdom of the Netherlands-Aruba : 2002 Article IV Consultation-Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This 2002 Article IV Consultation for the Kingdom of the Netherlands-Aruba highlights that after growing at more than 4 percent per year in 1996-2000, the Aruba economy experienced two years of retrenchment, with GDP falling an estimated 1.2 percent in 2001 and 3.8 percent in 2002. This downturn reflected a lull in investment activity, but especially weak tourism following the United States recession and the terrorist attacks of September 11, 2001. In 2003, sharply higher private and public investment and a modest revival in tourism should boost economic growth to more than 4 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet